2010
DOI: 10.1007/s11325-010-0436-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gender on continuous positive airway pressure requirements in patients with obstructive sleep apnea syndrome

Abstract: Men with OSA are more likely to require higher levels of CPAP support than women. The effect of gender on CPAP requirement persisted even after correcting for the severity of OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 21 publications
1
16
3
Order By: Relevance
“…A cross-sectional Japanese case-control study, however, observed that female patients require significantly lower levels of CPAP than male patients matched for BMI [44]. A more recent US study confirmed these findings and the effect of gender persisted after correction for the severity of OSA [45]. This observation is in line with evidence of a lower pharyngeal critical closing pressure in women.…”
Section: Symptoms Of Osas In Men and Women !mentioning
confidence: 66%
“…A cross-sectional Japanese case-control study, however, observed that female patients require significantly lower levels of CPAP than male patients matched for BMI [44]. A more recent US study confirmed these findings and the effect of gender persisted after correction for the severity of OSA [45]. This observation is in line with evidence of a lower pharyngeal critical closing pressure in women.…”
Section: Symptoms Of Osas In Men and Women !mentioning
confidence: 66%
“…77,78 The positive airway pressure (PAP) requirements however seem to be higher for males than females, after adjusting for baseline OSA severity and BMI. 79,80 No significant difference has been observed in terms of types of interface used or satisfaction with mask treatment in males and females. 81 Studies are ongoing to determine the efficacy of PAP devices that have algorithms targeting femalespecific characteristics.…”
Section: Treatmentmentioning
confidence: 95%
“…Regardless of the patient’s gender, there is also significant night-to-night variation in OSA, based on factors such as body posture, sleep stages, and previous drug or alcohol intake [ 28 ]. Besides OSA pathophysiology, gender influences also patients’ PAP requirements [ 29 ], as generally female patients require lower pressures. Such considerable variability between phenotypes highlights the relevance of the simulation approach taken in this study.…”
Section: Discussionmentioning
confidence: 99%